Attitudes Expressed in Online Comments about Environmental Factors in the Tourism Sector: An Exploratory Study - Saura, José Ramón; Palos-Sánchez, Pedro R; Rios Martin, Miguel Angel (International Journal of Environmental Research and Public Health, 2018)
The object of this exploratory study is to identify the positive, neutral and negative environment factors that affect users who visit Spanish hotels in order to help the hotel managers decide how to improve the quality of the services provided. To carry out the research a Sentiment Analysis was initially performed, grouping the sample of tweets (n = 14459) according to the feelings shown and then a textual analysis was used to identify the key environment factors in these feelings using the qualitative analysis software Nvivo (QSR International, Melbourne, Australia). The results of the exploratory study present the key environment factors that affect the users experience when visiting hotels in Spain, such as actions that support local traditions and products, the maintenance of rural areas respecting the local environment and nature, or respecting air quality in the areas where hotels have facilities and offer services. The conclusions of the research can help hotels improve their services and the impact on the environment, as well as improving the visitors experience based on the positive, neutral and negative environment factors which the visitors themselves identified.
Keywords: environment; sentiment analysis; Nvivo; Twitter; textual analysis; JCR; Scopus